The life satisfaction approach to estimating the cost of crime: An individual's willingness-to-pay for crime reduction - Manning, M; Ambrey, C; Fleming, C. M. (Griffith University, 2013)
This paper is motivated by the need to develop an improved model for estimating the intangible costs of crime. Such a model will assist policy makers and criminal justice researchers to compare the costs and benefits of crime control policies. We demonstrate how the life satisfaction approach may be used to measure an individual’s willingness-to-pay for crime reduction. Results indicate that property crime in one’s local area detracts from an individual’s life satisfaction. On average, an individual is implicitly willing-to-pay $3,213 in terms of annual household income to decrease the annual level of property crime by one offence per 1000 residents in their local area. This equates to a per-capita willingness-to-pay of $1,236.
Discussion Paper Series in Economics and Business Statistics
Keywords: Satisfaction -- Life; Life Events -- Crime; Disadvantage, adversity and resilience; Life Events; Satisfaction; Crime; Life; Dsiadvantage, adversity and resilience; Adversity and resilience